Results of ultra sound guided ovulation induction with high dose clomiphene citrate or injectable gonadotrophins and intrauterine insemination (IUI) - Wijeyaratne, C N; Wijerathne, S; Randeniya, C C; Seneviratne, H R (The Sri Lanka College of Obstetricians and Gynaecologists, 1996)
OBJECTIVE We present the results of ultrasound guided induction of ovulation (with high dose of clomiphene or gonadotrophins combined with Human Chorionic Gonadotrophin injection) and IUI with sperm concentrate. METHODOLOGY A total of 32 women were recruited over a period of two years. All couples had undergone a minimum of 6 cycles of clomiphene citrate 50-100mg ovulation induction previously. Fifteen of their partners has oligoasthenozoospermia. Four patients has polycystic ovarian disease resistant to high dose clomiphene, with normal male factor. Five couples had unexplained infertility. Twenty-eight women were prescribed clomiphene 150-200 mg and follicular measurements carried out at mid-cycle by vaginal ultrasound. Four were given low dose FSH injections daily with frequent serum estradiol and ultrasound measurements. Human chorionic injection was given for those with mature follicle and IUI of sperm concentrates carried out on'two occasions. Luteal phase progesterone was carried out to confirm ovulation. RESULTS: A total of 96 clomiphene treatment cycles were carried out. 22 (78 percent) ovulated and 8 (28 percent) conceived. One cycle was abandoned due to mild ovarian hyper-stimulation (OHSS). The average number of cycles for those who conceived was 3. Four of their partners had oligoasthenozoospermia. A total of 10 cycles were induced with FSH injections. Two cycles were abandoned due to OHSS. One patient had an ectopic pregnancy and another conceived an intrauterine pregnancy at her second cycle.
Keywords: Ultra Sound; Ovulation Induction; Clomiphene Citrate; IUI